2017
DOI: 10.1002/phar.2034
|View full text |Cite
|
Sign up to set email alerts
|

Early Administration of Adjuvant β‐Lactam Therapy in Combination with Vancomycin among Patients with Methicillin‐Resistant Staphylococcus aureus Bloodstream Infection: A Retrospective, Multicenter Analysis

Abstract: Receipt of COMBO therapy did not decrease the rate of clinical failure but was associated with expedited bacteremia clearance. Early adjuvant β-lactam therapy deserves continued evaluation and clinical consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Although there was no difference in mortality and metastatic infection, the mean duration of bacteraemia in the combination therapy group was 1.94 days compared to 3 days in the standard group (ratio of means 0.65, 95% CI 0.41‐1.02) . Another retrospective study which evaluated 97 patients demonstrated similar outcomes in which β‐lactam plus vancomycin combination compared to vancomycin monotherapy resulted in improvements to bacteraemia clearance (median time to clearance of 3 days vs 4 days, respectively, P = 0.047) with no improvements in treatment failures (24.6% vs 30%, respectively, P = 0.55) . Trinh et al found that vancomycin plus cefazolin compared to vancomycin monotherapy resulted in fewer treatment failures (24% vs 52%, respectively, P = 0.006) and fewer cases of persistent MRSA bacteraemia (15% vs 35%, respectively, P = 0.023).…”
Section: Resultsmentioning
confidence: 94%
“…Although there was no difference in mortality and metastatic infection, the mean duration of bacteraemia in the combination therapy group was 1.94 days compared to 3 days in the standard group (ratio of means 0.65, 95% CI 0.41‐1.02) . Another retrospective study which evaluated 97 patients demonstrated similar outcomes in which β‐lactam plus vancomycin combination compared to vancomycin monotherapy resulted in improvements to bacteraemia clearance (median time to clearance of 3 days vs 4 days, respectively, P = 0.047) with no improvements in treatment failures (24.6% vs 30%, respectively, P = 0.55) . Trinh et al found that vancomycin plus cefazolin compared to vancomycin monotherapy resulted in fewer treatment failures (24% vs 52%, respectively, P = 0.006) and fewer cases of persistent MRSA bacteraemia (15% vs 35%, respectively, P = 0.023).…”
Section: Resultsmentioning
confidence: 94%
“…1 ). After applying the inclusion/exclusion criteria, a total of 15 studies ( 6 , 18 31 ) comprising a total of 2,594 patients were included (1,189 patients in the standard therapy [STAN] group and 1,405 patients in the STAN therapy combined with β-lactams [COMBO] group), including 7 studies ( 21 27 ) based on the combination of VAN, 5 studies ( 6 , 28 31 ) based on the combination of DAP, and 3 studies ( 18 20 ) based on the combination of daptomycin or vancomycin. Among the included studies, the β-lactam of choice was ceftaroline in four studies ( 20 , 29 31 ), cefazolin in three studies ( 19 , 23 , 25 ), flucloxacillin in two studies ( 19 , 22 ), cloxacillin in one study ( 19 ), and cefepime in one study ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, the β-lactam of choice was ceftaroline in four studies ( 20 , 29 31 ), cefazolin in three studies ( 19 , 23 , 25 ), flucloxacillin in two studies ( 19 , 22 ), cloxacillin in one study ( 19 ), and cefepime in one study ( 27 ). In six cohort studies, β-lactams generally comprised more than 3 antibacterial agents ( 18 , 21 , 26 , 28 ) or unknown varieties ( 6 , 24 ). Among the included studies, 3 were randomized controlled trials (RCTs) ( 19 , 22 , 30 ), 12 were retrospective cohort studies, 10 were multicenter studies, 4 were conducted at a single center, and 1 was unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent antistaphylococcal antibiotics such as ceftaroline (approved for acute bacterial skin and skin structure infection [ABSSSI] and communityacquired bacterial pneumonia [CABP] [25]) and telavancin (approved for ABSSSI and hospital-acquired bacterial pneumonia [HABP] [26]) are used as salvage therapy or in combination therapy to treat complicated S. aureus infections. Combination therapy with beta-lactams for MRSA infections results in more rapid clearance of S. aureus from the blood (27,28), but this has not translated into improved clinical outcomes (29). The recent ARREST trial in patients with S. aureus bacteremia, which assessed the superiority of adjunctive rifampin in combination with SOC antibiotics to SOC antibiotics alone, showed a positive trend toward reducing infection recurrence in patients treated with adjunctive rifampin (23).…”
Section: Discussionmentioning
confidence: 99%